2017
DOI: 10.1021/acsbiomaterials.7b00549
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Hyaluronate–Hollow Gold Nanosphere Conjugate for Anti-Obesity Photothermal Lipolysis

Abstract: Obesity is associated with the risk of developing several severe diseases, such as metabolic disorder, diabetes, and heart diseases. Despite wide investigation and trials, a noninvasive obesity therapy is still an important medical unmet need, targeting the abnormal adipose tissue. Here, we developed hyaluronate–hollow gold nanosphere–adipocyte-targeting peptide (HA–HAuNS–ATP) conjugates for the photothermal ablation of adipose tissues. The HA–HAuNS–ATP conjugate could be noninvasively delivered into the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…This study demonstrated the potential use of laser-based lipolysis for reduction of fat within the WAT, and for treatment of obesity [102]. However, these procedures are highly invasive, uncomfortable, painful, takes a long time to recover, causes deformities, and lumpy skin due to seromas [18, 19, 102]. These procedures can be improved through the use of nano-based thermal agents to reduce discomfort, and laser-induced tissue damage.…”
Section: Nanotechnology-based Photothermal Lipolysismentioning
confidence: 99%
See 3 more Smart Citations
“…This study demonstrated the potential use of laser-based lipolysis for reduction of fat within the WAT, and for treatment of obesity [102]. However, these procedures are highly invasive, uncomfortable, painful, takes a long time to recover, causes deformities, and lumpy skin due to seromas [18, 19, 102]. These procedures can be improved through the use of nano-based thermal agents to reduce discomfort, and laser-induced tissue damage.…”
Section: Nanotechnology-based Photothermal Lipolysismentioning
confidence: 99%
“…Their physico-chemical properties can be altered by attaching various molecules on the NPs. For instance, a dual targeted hollow AuNSs were able to pass through the three layers of the skin non-invasively, and through PTT, was able to induce adipocyte cell death in mice [18]. Hyaluronic acid (HA) attached to the hollow AuNSs allowed transdermal delivery of the NPs to the target tissue.…”
Section: Nanotechnology-based Photothermal Lipolysismentioning
confidence: 99%
See 2 more Smart Citations
“…To resolve the above issues, we have developed the transdermal drug delivery platform for the treatment of alopecia using MXD encapsulated Hyaluronate -Poly(-Lactide-co-Glycolide) nanoparticles (HA-PLGA/MXD NPs). Hyaluronic acid (HA) is a well-known natural polysaccharide for various biomedical applications [11][12][13][14][15][16][17]. The excellent characteristic of HA for the transdermal delivery has been reported in our previous works [12].…”
Section: Introductionmentioning
confidence: 99%